Development and application of unplanned automatic shutdown fault tree model of nuclear power plant. Issue 1 (1st November 2022) - Cheng, Bin; Yang, Xiaohu; Qing, Chen; Jiang, Hong
Abstract : In order to improve the operation performance of nuclear power plants, this paper introduces a modeling method of unplanned automatic shutdown of nuclear power units based on Fault Tree Analysis, and takes the shutdown signal of steam generator water level low-low as an example, analyzes the development process and application scenarios of unplanned automatic shutdown fault tree in detail. The results show that this method solves the huge and complex problems in the fault tree model of unplanned automatic shutdown in nuclear power units, and can be used to comprehensively and systematically identify the components that affect unit power generation. At the same time, combined with quantitative data, it can monitor the risk of unit power generation, and achieve targeted and efficient improvement of equipment reliability management level and power generation performance level.